Editorial Reflections on Philosophizing in Music Education - Jorgensen, Estelle R; Yob, Iris M (Philosophy of music education review, 2023)
WRITING PHILOSOPHY Like other subject areas in the academy, philosophy has its own intellectual structure, a canon of significant writings, its own interpretative methods, and its distinctive role and purpose. Using inference, pattern-seeking, deduction, hypotheses, statistical analysis, and so on, these activities result in claims, interpretations, and theories that give meaning to what we see, hear, and feel. When those ideas relate to a practical Held, such as education, musicmaking, or teacher education, philosophical analysis can sharpen interpretations and theories and thereby strengthen their implications for practice. Typically, a philosophical study will compare and contrast theoretical approaches, describe patterns and call out themes in a body of knowledge, underscore the conscious and unconscious assumptions behind a claim, reveal perspectives from various schools of thought and highlight their limitations and delimitations, offer critical appraisal of the strengths and weaknesses of claims, and make other similar contributions to theory development and interpretation.